2020
DOI: 10.1177/0309324720971140
|View full text |Cite
|
Sign up to set email alerts
|

The validation of a full-field deformation analysis of an aircraft panel: A case study

Abstract: The increased use of optical measurement techniques in industrial environments has the potential to increase knowledge and creates an opportunity for a more comprehensive validation of computational predictions. In this paper, a quantitative validation methodology is applied to a 1 m × 1 m panel from an aircraft fuselage subject to compression and torsion, in order to evaluate the predicted response of the panel. A test matrix with four loading cases, namely pre-buckling and post-buckling compression with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The case study represents a further step on the path from the research laboratory, as represented by the initial work on the methodology by Sebastian et al 13 and the inter-laboratory study reported by Hack et al, 7 via the large-scale study of an industrial component in a laboratory described recently by Dvurecenska et al, 14 to a ground-test on an aircraft fuselage at the manufacturer's site. This represents a progressive rise in the technology readiness level of this approach to the validation process for computational solid mechanics models and the resolution of a number of issues that had been identified during this transition from research laboratory to industry.…”
Section: Discussionmentioning
confidence: 99%
“…The case study represents a further step on the path from the research laboratory, as represented by the initial work on the methodology by Sebastian et al 13 and the inter-laboratory study reported by Hack et al, 7 via the large-scale study of an industrial component in a laboratory described recently by Dvurecenska et al, 14 to a ground-test on an aircraft fuselage at the manufacturer's site. This represents a progressive rise in the technology readiness level of this approach to the validation process for computational solid mechanics models and the resolution of a number of issues that had been identified during this transition from research laboratory to industry.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [21] proposed new cross-scale method to predict the structural deformation of aircraft materials, and the method has been applied to multiple stages of multiple assembly and achieved good results. Dvurecenska et al [22] use image decomposition analyzed the feature vectors of different aircraft deformations, and evaluated the relationship between the curvature of deformations. Sagadeev et al [23] proposed a method for monitoring the deformation of aircraft structure using optical fiber sensing and measurement technology.…”
Section: Aircraft Deformation Analysismentioning
confidence: 99%